2020
DOI: 10.4012/dmj.2018-358
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization of monolithic zirconia submitted to different surface treatments applying optical interferometry and raman spectrometry

Abstract: This study evaluated roughness parameters and phase transformation of monolithic zirconia ceramics after various mechanical and laser thermal treatments. Fully sintered monolithic zirconia cylinder specimens were divided to five groups, according to the applied surface treatment: CL: control, GB: grit-blasted with glass particles. AL50: grit-blasted with 50 μm alumina particles, AL90: gritblasted with 90 μm dyed-alumina particles and FEML: subjected to femto laser thermal treatment. Six roughness parameters (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…It was expected that alumina abrasion with particles of larger size would result in a rougher surface, assisting micromechanical retention [32]. Indeed, the SEM micrographs and roughness measurements reported in our previous study showed that AL90 specimens had rougher surfaces (AL50 = 340.3 ± 49.2 nm) as compared to AL50 (AL90 = 1155.1 ± 97.76 nm) [27]. EDS analysis showed the increased Al and O content in both groups, probably due to the inclusion of Al 2 O 3 particles onto the ceramic surfaces during alumina air-abrasion.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…It was expected that alumina abrasion with particles of larger size would result in a rougher surface, assisting micromechanical retention [32]. Indeed, the SEM micrographs and roughness measurements reported in our previous study showed that AL90 specimens had rougher surfaces (AL50 = 340.3 ± 49.2 nm) as compared to AL50 (AL90 = 1155.1 ± 97.76 nm) [27]. EDS analysis showed the increased Al and O content in both groups, probably due to the inclusion of Al 2 O 3 particles onto the ceramic surfaces during alumina air-abrasion.…”
Section: Discussionmentioning
confidence: 80%
“…The GB group presented very low shear strengths and very small percentages of the resin material remained on the surface, resulting in a high percentage of adhesive fracture mode. Based on our previous study and SEM analysis, it was observed that GB created a smooth surface with slightly higher toughness than the control (GB = 99.4 ± 16.6 nm, CL = 73.9 ± 10.7 nm) [27], likely because glass particles are much softer than alumina or zirconia. Therefore, another mechanism, irrespective of roughness, was responsible for these values.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations